Galvanic Deposition of Pt Nanoparticles on Black TiO2 Nanotubes for Hydrogen Evolving Cathodes. Issue 22 (6th October 2021) - Touni, Aikaterini; Liu, Xin; Kang, Xiaolan; Carvalho, Patricia A.; Diplas, Spyros; Both, Kevin G.; Sotiropoulos, Sotirios; Chatzitakis, Athanasios
Abstract: A galvanic deposition method for the in‐situ formation of Pt nanoparticles (NPs) on top and inner surfaces of high‐aspect‐ratio black TiO2 ‐nanotube electrodes (bTNTs) for true utilization of their total surface area has been developed. Density functional theory calculations indicated that the deposition of Pt NPs was favored on bTNTs with a preferred [004] orientation and a deposition mechanism occurring via oxygen vacancies, where electrons were localized. High‐resolution transmission electron microscopy images revealed a graded deposition of Pt NPs with an average diameter of around 2.5 nm along the complete nanotube axis (length/pore diameter of 130 : 1). Hydrogen evolution reaction (HER) studies in acidic electrolytes showed comparable results to bulk Pt (per geometric area) and Pt/C commercial catalysts (per mg of Pt). The presented novel HER cathodes of minimal engineering and low noble metal loadings (μg cm −2 range) achieved low Tafel slopes (30–34 mV dec −1 ) and high stability in acidic conditions. This study provides important insights for the in‐situ formation and deposition of NPs in high‐aspect‐ratio structures for energy applications. Abstract : Be spontaneous : Pt nanoparticles of a diameter of around 2 nm are deposited on black TiO2 nanotubes via the spontaneous galvanic deposition process, across the whole nanotube length truly utilizing the structure's high‐aspect‐ratio surface area. These electrodes of minimal engineering and low noble metal loadings show high activity and stability towards the hydrogen evolution reaction in acid.